Biophysical properties of human breast cancer cells measured using silicon MEMS resonators and atomic force microscopy. Issue 3 (4th December 2014) - Corbin, Elise A.; Kong, Fang; Lim, Chwee Teck; King, William P.; Bashir, Rashid
Abstract : Biophysical studies on individual cells can help to establish the relationship between mechanics and biological function. Abstract : Biophysical studies on individual cells can help to establish the relationship between mechanics and biological function. In the case of cancer, mechanical properties of cells have been linked to metastatic activity and disease progression and can be crucial for understanding cellular physiology and metabolism. In this study, we report measurements of the stiffness of breast cancer cells using a novel silicon MEMS resonant sensor and validated the results with atomic force microscopy (AFM). We measured the mass and stiffness of individual benign (MCF-10A), non-invasive malignant (MCF-7), and highly-invasive malignant (MDA-MB-231) breast cancer cells using the silicon resonant MEMS sensors. The sensor extracts the average stiffness value of the whole cell and allows comparison of stiffness of different cell types. We found differences between the cell lines in both elasticity and viscosity, and confirmed our observations through independent measurements with atomic force microscopy (AFM). Coupled with measurements over time, this approach could lead to a multimodal investigation of both growth and physical properties of single cells. The mechanical property sensitivity and resolution of these pedestal sensors were investigated to understand the significance of the frequency shift during operation. The lowest achievable spring constant and damping constant resolutions have a range of 0.06 to 17.10 mN m −1 and 1.63 to 1.96 nN s m −1, respectively, measured across the range of physiological cell mechanical properties.